2020
DOI: 10.1177/0022034520905660
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of Alveolar Ridge Preservation: A Randomized Controlled Trial

Abstract: Alveolar ridge preservation (ARP) therapy is indicated to attenuate the physiologic resorptive events that occur as a consequence of tooth extraction with the purpose of facilitating tooth replacement therapy. This randomized controlled trial was primarily aimed at testing the efficacy of ARP as compared with unassisted socket healing. A secondary objective was to evaluate the effect that local phenotypic factors play in the volumetric reduction of the alveolar bone. A total of 53 subjects completed the study.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

17
131
2

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 83 publications
(171 citation statements)
references
References 22 publications
17
131
2
Order By: Relevance
“…Considering that ARP outcomes can vary substantially across different sites (Avila-Ortiz, Elangovan, Kramer, Blanchette, & Dawson, 2014;Iocca, Farcomeni, Pardinas Lopez, & Talib, 2017), site-specific factors can play a major role (Avila-Ortiz, Chambrone, & Vignoletti, 2019). Specifically, it has been shown that 0.6 mm of baseline buccal bone thickness is associated with at least 10% bone volume loss in sites receiving ARP (Avila-Ortiz et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…Considering that ARP outcomes can vary substantially across different sites (Avila-Ortiz, Elangovan, Kramer, Blanchette, & Dawson, 2014;Iocca, Farcomeni, Pardinas Lopez, & Talib, 2017), site-specific factors can play a major role (Avila-Ortiz, Chambrone, & Vignoletti, 2019). Specifically, it has been shown that 0.6 mm of baseline buccal bone thickness is associated with at least 10% bone volume loss in sites receiving ARP (Avila-Ortiz et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…Differences in horizontal bone changes between baseline and final follow-up assessed in CBCT scan images were reported in eleven studies (Avila-Ortiz et al, 2020 ;Canellas et al, 2020 ;Cha et al, 2019 ;Clementini et al, 2019 ;Fiorellini et al, 2005 ;Jiang et al, 2017 ;Jung et al, 2013 ;Lim et al, 2019 ;Pang et al, 2016 ;Qabbani et al, 2017 ;Sun et al, 2019 ). Seven studies assessed horizontal changes at different levels (i.e.…”
Section: Radiographic Horizontal Bone Changesmentioning
confidence: 99%
“…Differences in bone volumetric changes between baseline and final follow-up assessed by CBCT scan images were reported in two studies including non-molar teeth (Avila-Ortiz et al, 2020 ;Canellas et al, 2020…”
Section: Volumetric Bone Changes Assessed In Dicom Filesmentioning
confidence: 99%
See 1 more Smart Citation
“…It is dependent on a host of local and systemic factors [ 1 ]. Studies have previously used in-vivo cone beam computed tomographic (CBCT) scanning or extraoral surface scanning of patient casts to monitor and quantify bone remodelling up to four months post-extraction [ 2 , 3 ]. Indeed, a recent study involving ten patients demonstrated the use of CBCT to measure volumetric changes post vertical ridge augmentation in the form of vertical bone gain, planned bone volume, lacking bone volume, and regenerated bone volume, using computer-aided design/computer-aided manufacturing customised titanium meshes [ 4 ].…”
Section: Introductionmentioning
confidence: 99%